Sedimentological and geomorphological characteristics of Quaternary deposits in the Planica-Tamar Valley in the Julian Alps (NW Slovenia). Issue 2 (13th November 2018) - Novak, Andrej; Popit, Tomislav; Šmuc, Andrej
ABSTRACT: We present a geomorphological map on a scale of 1:15, 000, with detailed sedimentological descriptions, and a general relative spatio-temporal depositional reconstruction of Quaternary sediments in the Planica-Tamar Valley (NW Slovenia). After the Last Glacial Maximum, the retreating Quaternary glacier deposited large amounts of glacial sediments. These were followed by Holocene sediments, which differ in their sedimentological characteristics, transport mechanisms, and morphology. These sediments are deposited as sedimentary bodies with complex depositional geometries. They form areas of active, partly active, and inactive sedimentation in response to local/regional climate and bedrock geology. Previous research of the valley was mainly focused on bedrock mapping, while almost completely neglecting Quaternary deposits. This work is the first broader analysis of Quaternary sedimentary deposits in the research area, which offers an insight into the complex geomorphological and sedimentological processes, which shape the current mountainous landscape.